A CORRECTION TO “Patterns and trends in research on external public debt management” - Mila Razinkova; Tetiana Grynko; Natalia Nebaba; Rostislav Botvinov; Dmytro Pryimachenko (Public and Municipal Finance, 2025)
The Original Article was published on January 16, 2024 CorrectionIn the LITERATURE REVIEW section of this article, the following adjustments were made:In paragraph 7, the following sentences were added: “Empirical evidence also suggests that fluctuations in the money supply and exchange rates can significantly affect a country's ability to service its external public debt, especially in developing economies (Aid & Benelbar, 2023)” and “Moreover, studies underline the necessity of introducing adaptive management practices within public financial institutions to ensure responsive and efficient handling of external public debt (Grynko & Gviniashvili, 2015).” In paragraph 8, the following sentence was added: “An important factor affecting external debt dynamics in Ukraine is the functioning of systemically important domestic banks, which influence both the demand for sovereign borrowing and its sustainability (Buriak et al., 2015). In the REFERENCES section, the below listed sources were deleted: Bensaad, A., & Azzazi, S. (2023). The impact of monetary policy tools in achieving monetary stability in Algeria: Approach by the ARDL model. Financial Markets, Institutions and Risks, 7(2), 28-45. https://doi.org/10.21272/fmir.7(2).28-45.2023 Gentsoudi, V. (2023). The impact of effective leadership on public sector’s financial instruments: Empirical evidence from Greece. Business Ethics and Leadership, 7(2), 47-54. https://doi.org/10.21272/bel.7(2).47-54.2023 Gontareva, I., Litvinov, O., Hrebennyk, N., Nebaba, N., Litvinova, V., & Chimshir, A. (2022). Improvement of the innovative ecosystem at universities. Eastern-European Journal of Enterprise Technologies, 1(13(115)), 59-68. https://doi.org/10.15587/1729-4061.2022.251799 Kaya, H. D. (2023). The impact of the 2008–2009 global crisis on loan applications and access to finance. Financial Markets, Institutions and Risks, 7(2), 12-17. https://doi.org/10.21272/fmir.7(2).12-17.2023 Khouiled, B., Chini, S.-E., & Benrouina, M. (2023). Dynamic relationship between exchange rate and trade balance. SocioEconomic Challenges, 7(3), 164-173. https://doi.org/10.61093/sec.7(3).164-173.2023 Korneyev, M., Berezhniuk, I., Dzhyndzhoian, V., Kubakh, T., & Horb, K. (2022). Business marketing activities in Ukraine during wartime. Innovative Marketing, 18(3), 48-58. https://doi.org/10.21511/im.18(3).2022.05 Kozmenko, S., & Korneev, M. (2014). Periodization of financialization process of economics: Domestic and foreign contexts. Economic Annals-XXI, 9-10(1), 73-76. Retrieved from http://ea21journal.world/index.php/ea-v144-18/ Leonov, S. V., Vasylieva, T. A., & Tsyganyuk, D. L. (2012). Formalizatsiia funktsionalnykh obmezhen diialnosti instytutiv spilnoho investuvannia naosnovi porivnialnoho analizu finansovykh rynkiv krain hrupy FM CEEC [Formalization of functional limitations in functioning of co-investment funds basing on comparative analysis of financial markets within FM CEEC]. Actual Problems of Economics, 134(8), 75-85. (In Ukrainian). Retrieved from http://essuir.sumdu.edu.ua/handle/123456789/57569 Lyeonov, S., Vasilyeva, T., Bilan, Y., & Bagmet, K. (2021). Convergence of the institutional quality of the social sector: The path to inclusive growth. International Journal of Trade and Global Markets, 14(3), 272-291. https://doi.org/10.1504/IJTGM.2021.115712 Maile, K. V., & Vyas-Doorgapersad, S. (2023). Misconduct impeding good governance in the South African public service. Business Ethics and Leadership, 7(2), 9-17. https://doi.org/10.21272/bel.7(2).9-17.2023 Makedon, V., & Korneyev, M. (2014). Improving methodology of estimating value of financial sector entities dealing in mergers and acquisitions. Investment Management and Financial Innovations, 11(1), 44-55. Retrieved from https://www.businessperspectives.org/images/pdf/applications/publishing/templates/article/assets/5607/imfi_en_2014_01_Makedon.pdf Naumenkova, S., Mishchenko, V., Chugunov, I., & Mishchenko, S. (2023). Debt-for-nature or climate swaps in public finance management. Problems and Perspectives in Management, 21(3), 698-713. https://doi.org/10.21511/ppm.21(3).2023.54 Reinhart, C. M., & Rogoff, K. S. (2009). This time is different: Eight centuries of financial folly. Princeton University Press. https://doi.org/10.2307/j.ctvcm4gqx Sardak, S., Korneyev, M., Simakhova, A., & Bilskaya, O. (2017). Global factors which influence the directions of social development. Problems and Perspectives in Management, 15(3), 323-333. http://dx.doi.org/10.21511/ppm.15(3-2).2017.02 Zhuravka, F., Filatova, Н., & Aiyedogbon, J. O. (2019). Government debt forecasting based on the Arima model. Public and Municipal Finance, 8(1), 120-127. https://doi.org/10.21511/pmf.08(1).2019.11